2018
DOI: 10.1257/jep.32.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Homeownership and the American Dream

Abstract: For decades, it was taken as a given that an increased homeownership rate was a desirable goal. But after the financial crises and Great Recession, in which roughly eight million homes were foreclosed on and about $7 trillion in home equity was erased, economists and policymakers are re-evaluating the role of homeownership in the American Dream. Many question whether the American Dream should really include homeownership or instead focus more on other aspects of upward mobility, and most acknowledge that homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(98 citation statements)
references
References 37 publications
3
89
0
6
Order By: Relevance
“…The estimates for the education level controls are also consistent with the existing empirical results, since higher levels of education are related to greater probabilities of home-ownership (Coulson, 1999;Constant et al, 2009;Goodman and Mayer, 2018). Being single or never married decreases the probability of owning one's own dwelling.…”
Section: 1baseline Modelsupporting
confidence: 85%
See 2 more Smart Citations
“…The estimates for the education level controls are also consistent with the existing empirical results, since higher levels of education are related to greater probabilities of home-ownership (Coulson, 1999;Constant et al, 2009;Goodman and Mayer, 2018). Being single or never married decreases the probability of owning one's own dwelling.…”
Section: 1baseline Modelsupporting
confidence: 85%
“…This is calculated using the IPUMS International. The average of homeowners is 70 percent, which is quite similar to that presented in Goodman and Mayer (2018) for the year 2015 (at 69.6 percent). As mentioned above, although many factors can determine those home-ownership dissimilarities, it is possible to argue that housing tenure outcomes cannot only be explained within a standard framework that accounts only for socio-economic, demographic, and housing market characteristics.…”
Section: Sectionsupporting
confidence: 78%
See 1 more Smart Citation
“…Goodman and Mayer () suggest that the evidence used to argue against minority homeownership is inconclusive and that with appropriate mortgage regulation in place, more households should be able to benefit from homeownership. Along these lines, Grinstein‐Weiss et al.…”
Section: Evidence On the Financial Pros And Cons Of Black Homeownershipmentioning
confidence: 99%
“…In a recovering market, it might be expected that owner estimates lag true market values (Bucholz et al 2016). Goodman and Mayer (2018) suggest that the evidence used to argue against minority homeownership is inconclusive and that with appropriate mortgage regulation in place, more households should be able to benefit from homeownership. Along these lines, Grinstein-Weiss et al (2013) found that even during the calamitous period of 2005 to 2008, low-and medium-income homeowners receiving prime loans accumulated more assets than did otherwise similar renters.…”
Section: Evidence On the Financial Pros And Cons Of Black Homeownershipmentioning
confidence: 99%